Analisis Penilaian Proyek Penanaman Modal untuk Penambahan BUS dengan Metode Net Present Value pada PO. Telaga Biru Putra Pagar Alam - Zulaiha (Jurnal Manajemen dan Bisnis, 2020)
This study aims to determine and analyze how the analysis of investment project assessments for bus additions using the Net Present Value at Po. TelagaBiru Putra PagarAlam ". The results of the study were based on a quantitative analysis of Operational Cash flow at Po. TelagaBiru Putra PagarAlam, namely to estimate cash flow, it is necessary to determine the estimated period / time, and this is adjusted to the life of the project for the next 5 years. Outside this period, the project is considered to be no longer profitable. Because the amount of costs will exceed income. It is predicted that in 2009 net cash inflow will be received of Rp. 542,818,018, - increased in 2010 to 569,433,437, - increased in 2011 to 583,852,265, - and increased again in 2012 to 636,454,673, - and in 2013 after determining the residual value to be Rp. 892.836.049, - these values are used in determining the Net Present Value.